THINKING STYLES INVENTORY ADAPTATION AND STANDARDIZATION IN LATVIAN - Šteinberga, Airisa; Hofmane, Anete; Koroļeva, Ilze; Zakriževska-Belogrudova, Maija; Barone, Lelde (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
Thinking styles are defined as consistent individual differences in preferred ways of organizing and processing information and experience, thus bridging the gap between personality traits and cognitive processes, meaning, it is more important to understand what abilities people prefer to develop and use, rather than what abilities they have. Thinking styles remain an ongoing area of research in education and psychology, providing insights into students’ experiences and informing educational practices. Latvia still faces a shortage of validated and standardized tests, thus to determine thinking styles, a questionnaire titled “Thinking Style Inventory – Revised II” was selected. This research is a part of a much wider study, which is based on the idea that nowadays the use of the internet and technology form and develop young people’s habits of mind that have not yet been explored. Based on this idea, a research project was established whose overall goal is to discover the impact of young people’s (age 16-25) internet use patterns on cognitive functioning (The impact of internet usage patterns on the development of youth’s cognitive styles, No.: lzp-2021/1-0357). The goal of the specific stage of the study and thus this article is to adapt and standardize the Thinking Style Inventory–Revised II in Latvian. To reach the goal, the questionnaire underwent back and forth translation, then was piloted (n=30), checked for internal consistency, thus concluding the first stage of adaptation. For standardization (n=2169) factoranalysis, discrimination indexes and norms were determined. The results show an overall good internal consistency and the factoranalysis shows similar structure to the original questionnaire. The obtained results indicate that Thinking Style Inventory – Revised II Latvian version can be successfully used to determine thinking styles in Latvia.